Integrated ANP and TOPSIS Method for Supplier Performance Assessment - Christine Natalia; Ita Primsa Surbakti; Chendrasari Wahyu Oktavia (Jurnal Teknik Industri, 2020)
A supplier has become one of the main factors that influence a company's supply chain activities. Supplier assessment is vital as suppliers have different performance. This study aims at assessing supplier performance using the integration of ANP and TOPSIS methods. Supplier performance assessment was based on supplier criteria indicators. The weighting criteria used ANP was used to determine the most significant influence criteria of supplier performance. Furthermore,  TOPSIS was also employed to obtain supplier preference. Eight criteria and twenty-five sub-criteria were used for the supplier performance assessment.  The three highest sub-criteria were specification of quality, the flexibility of order changes, and production capacity. The priority results for suppliers were sorted from the highest to lowest ratio values.